2007
DOI: 10.1212/01.wnl.0000278071.91524.4d
|View full text |Cite
|
Sign up to set email alerts
|

How Common Are the “Common” Neurologic Disorders?

Abstract: Objective: To estimate the current incidence and prevalence in the United States of 12 neurologic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(18 citation statements)
references
References 259 publications
3
15
0
Order By: Relevance
“…6 These findings are also present in other studies, which reported a female predominance in the diagnosis of Headache and a higher peak of incidence of tension headache and migraine (the two main representatives of this group of diseases) between 20 and 40 years of age. 11,14 In addition to other factors such as age and regional characteristics, possibly the majority of women in our sample justifies the high frequency of Headache found in our study.…”
Section: Discussionsupporting
confidence: 58%
“…6 These findings are also present in other studies, which reported a female predominance in the diagnosis of Headache and a higher peak of incidence of tension headache and migraine (the two main representatives of this group of diseases) between 20 and 40 years of age. 11,14 In addition to other factors such as age and regional characteristics, possibly the majority of women in our sample justifies the high frequency of Headache found in our study.…”
Section: Discussionsupporting
confidence: 58%
“…By conservative estimates, 400,000 people live with MS in the United States today [1] and over 2.5 million people live with MS worldwide [2]. Each year, approximately 16,000 veterans with MS receive healthcare services from the Veterans Health Administration (VHA).…”
Section: Introductionmentioning
confidence: 99%
“…Neurodegenerative disorders are common and age-related. For example, there are 65 AD patients and 9.5 PD patients per 1000 elderly people in the United States, while the annual incidence of ALS is 1.6 [ 45 ]. There is much evidence that oxidative damage is involved in the pathogenesis of neurodegenerative disorders, including AD and PD [ 46 ].…”
Section: Relationship Between Rna Oxidation and Neurodegenerative mentioning
confidence: 99%